2005
DOI: 10.1021/ol0501727
|View full text |Cite
|
Sign up to set email alerts
|

Application of Microwave Irradiation to the Synthesis of 14-Helical β-Peptides

Abstract: [structure: see text] We have evaluated the effects of microwave irradiation on the solid-phase synthesis of beta-peptides. Sequences designed to adopt the 14-helix, especially those containing the structure-promoting residue trans-2-aminocyclohexanecarboxylic acid (ACHC), suffer from poor synthetic efficiency under standard SPPS conditions. A comparison of microwave and conventional heating shows that both provide excellent synthetic results for shorter sequences; however, we identify a clear benefit from mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 31 publications
2
93
0
3
Order By: Relevance
“…␣-Peptide 1 and ␣/␤-Peptides 2-5 were prepared by standard Fmoc automated solid phase synthesis. ␣/␤-Peptides 6-9 were prepared by microwave-assisted Fmoc solid-phase peptide synthesis (36,37). Detailed synthetic methods can be found in SI Text.…”
Section: Methodsmentioning
confidence: 99%
“…␣-Peptide 1 and ␣/␤-Peptides 2-5 were prepared by standard Fmoc automated solid phase synthesis. ␣/␤-Peptides 6-9 were prepared by microwave-assisted Fmoc solid-phase peptide synthesis (36,37). Detailed synthetic methods can be found in SI Text.…”
Section: Methodsmentioning
confidence: 99%
“…microwave (MW) irradiation has become a preferred choice for the organic chemist [1,[14][15][16]. There are many examples of the application of MW irradiation in peptide synthesis, including automated peptide synthesizers equipped with MW capability [17][18][19][20][21][22]. The main advantages of MW-assisted chemistry are shorter reaction times and higher yields.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies revealed that β-peptides enter HeLa cells via a dynamin-independent, ameloride-sensitive endocytotic entry mechanism similar to macropinocytosis. While both polyproline type II helices and β-peptides achieve the goal of cell permeability, the latter possesses the advantage of small size (MW, P14LRR = 2979 Da; Gellman β-peptide decamer 1 = 1485 Da) as well as demonstrated compatibility with microwave synthesis [17]. In addition, the synthesis of β 3 -amino acid monomers [18] is more straightforward than the pre-decoration of hydroxyproline.…”
Section: Introductionmentioning
confidence: 99%